Objective measures of the environment and physical activity--results of the environment and physical activity study in English adults. - Foster, C; Hillsdon, M; Jones, A; Grundy, C; Wilkinson, P; White, M; Sheehan, B; Wareham, N; Thorogood, M (2009)
BACKGROUND: Physical activity has been positively associated with a range of objectively measured environmental variables. We explored the relationship of walking and other categories of physical activity with objectively measured activity specific environmental variables in a U.K. population. METHODS: We used a geographical information system (GIS) and gender specific multivariate models to relate 13,927 participants' reported levels of physical activity with a range of measures of the environment. RESULTS: Access to green space and area levels of crime were not associated with walking for recreation. Distance to facilities had either no or only a small effect on the uptake of different activities. Odds ratios of cycling for leisure dropped as local traffic density increased for both genders. Compared with the lowest quartile for traffic density the likelihood of reporting any cycling for leisure was OR 0.42, (95% CI 0.32 to 0.52, P < .001) for women and OR 0.41, (95% CI 0.33 to 0.50, P < .001) for men in the highest quartile. CONCLUSIONS: We were unable to reproduce results observed in previous studies. Future research should use large representative population samples from multiple areas to maximize environmental variability and if feasible use both objective and subjective measures of physical activity and the environment.